Hydrogeochemical Dynamics and Response of Karst Catchment to Rainstorms in a Critical Zone Observatory (CZO), Southwest China - Qin, Caiqing; Ding, Hu; Li, Si-Liang; Yue, Fu-Jun; Wang, Zhong-Jun; Zeng, Jie (Frontiers in Water, 2020)
Karst water is vital for local drinking and irrigation but is susceptible to contamination. Hydrochemistry, which is highly related to carbonate weathering in karst catchments, can affect water quality and respond rapidly to climate change. In order to explore hydrogeochemical sources, dynamics and their responses to rainstorms, rainwater, throughfall, hillslope runoff, surface water and groundwater were sampled synchronously during rainstorms at a karst Critical Zone Observatory (CZO), Southwest China. Results showed that the total dissolved solids (TDS) concentration in throughfall increased by 30.1±8.0% relative to rainwater, but both throughfall and rainwater contributed little to TDS in surface water and groundwater compared with terrestrial sources. Hydrochemistry in surface water and groundwater were diluted by rainstorms but displayed chemostatic responses with different intensities to increasing discharge. This is possibly regulated by hydrogeological conditions, available sources of various solutes and the difference between solute concentrations before and after rainstorms. Ca2+ and Mg2+ dynamics were mainly regulated by carbonate weathering, gypsum dissolution and gypsum-induced dedolomitization (geological sources) also affect Ca2+, Mg2+ and SO42- in deep confined groundwater draining a gypsum stratum. For HCO3-, CO2 from respiration and microbiologic activities is one dominant contributor, especially for spring. The chemostatic behaviors of NO3-, Cl- and K+ were related to agricultural activities, especially in surface water. These controls on hydrochemistry may already exist as hillslope runoff occurs, which has be further demonstrated by principle component analysis (PCA). The heterogeneous permeability of epikarst can affect the mixture of groundwater from different sources and flowing pathways, enabling hydrochemistry at different hydrogeological conditions to display discrepant responses to rainstorms. The epikarst aquifer with high permeability is susceptible to changes in external environment, such as rainstorms and agricultural activities, increasing the potential risk of water environment problems (chronic pollution of nitrogen and high hardness of water) during a certain period. Drinking water safety thus deserve consideration in the agricultural karst catchment.